Acquired macular pigmentation of unknown etiology - Siriorn Udompanich (2020)
© 2019 Matrix Medical Communications. All rights reserved. Acquired macular pigmentation of unknown etiology is a new umbrella term that encompasses a group of diseases that, while having similar clinical and histological features, their true entities are controversial, and a global consensus regarding these conditions is still lacking. The conditions comprised by the term are ashy dermatosis, erythema dyschromicum perstans, lichen planus pigmentosus, and idiopathic eruptive macular pigmentation. In this review, we compare the clinical and histological features of these conditions that comprise aquired macular pimgentation of unknown etiology, as well as review their responses to treatment.